The role of lncRNAs and XIST in oral cancer - Liu, Huimin; Wang, Dongxu; Kan, Shaoning; Hao, Ming; Chang, Lu; Lu, Pengxu; Liu, Yangyang; Jin, Ye; Liu, Weiwei (Frontiers in Cell and Developmental Biology, 2022)
Long non-coding RNA (lncRNA) plays a significant role in the pathogenesis of many human malignant tumors, including oral cancer. LncRNA can act as a gene regulator in a variety of cancers. It regulates the growth of malignant cells via many cellular signal pathways such as the PI3K (phosphoinositide 3-kinase)/AKT (α-serine/threonine-protein kinase) pathway. In this review, we have analyzed the role of lncRNAs, such as lncRNA X inactive specific transcript (XIST), in oral cancer, including its effects on the proliferation, apoptosis, invasion, migration, and resistance to chemotherapy of oral cancer. We have also focused on the role of lncRNA XIST as the core of X chromosome inactivation. Here, we provide a brief overview of the role of many kinds of lncRNAs, including XIST, which provides a theoretical basis for the study of the role of XIST in oral cancer. Our review may provide a new direction for the study of the occurrence, development, and prognosis of oral cancer and provide a new target for its treatment.